2021
DOI: 10.3390/cancers13143546
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Echogenicity of a Breast Tumor Predicts the Response to Neoadjuvant Chemotherapy

Abstract: The aim of the study was to improve monitoring the treatment response in breast cancer patients undergoing neoadjuvant chemotherapy (NAC). The IRB approved this prospective study. Ultrasound examinations were performed prior to treatment and 7 days after four consecutive NAC cycles. Residual malignant cell (RMC) measurement at surgery was the standard of reference. Alteration in B-mode ultrasound (tumor echogenicity and volume) and the Kullback-Leibler divergence (kld), as a quantitative measure of amplitude d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…According to the literature [31][37], the assessment of the tumor response to NAC may be inaccurate after the first and fourth week of treatment and improve after the eighth week of treatment. It is in line with our own previous observations [13][14] that the results after the first and second NAC courses (first and fourth week of treatment, respectively) are poor and improve after the third NAC course (seventh week of treatment). This is also the case in this study, where results obtained before the third NAC course (Appendix) are significantly worse for both the reference method and the new one, and no improvement was observed compared to the reference method.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the literature [31][37], the assessment of the tumor response to NAC may be inaccurate after the first and fourth week of treatment and improve after the eighth week of treatment. It is in line with our own previous observations [13][14] that the results after the first and second NAC courses (first and fourth week of treatment, respectively) are poor and improve after the third NAC course (seventh week of treatment). This is also the case in this study, where results obtained before the third NAC course (Appendix) are significantly worse for both the reference method and the new one, and no improvement was observed compared to the reference method.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in the amplitude distribution of the ultrasonic signal scattered in the tumor after successive cycles of chemotherapy were also studied. The distributions were differentiated by the Kullback-Leibler divergence determined with respect to the distributions after the first NAC cycle [13] or with respect to the reference phantom [14]. The highest AUC (area under the receiver operating characteristic curve) was achieved after the 3rd NAC cycle, 0.92 and 0.91 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the observation and assessment of the level of changes in tissue echogenicity based on image analysis may be a great challenge, as its evaluation may be influenced by both the operator's experience and image settings. However, the approach proposed by Dobruch-Sobczak et al can be fully objective through using the IBC parameter which quantitatively provides information about the scattering properties of microstructures present in the medium and thus characterizes tissue echogenicity in a quantitative manner (29) . In another study, which was a continuation of the above-discussed topic, Dobruch-Sobczak et al confirmed this hypothesis (30) .…”
Section: Determination Methods Parameter Name and Definition Tissue F...mentioning
confidence: 99%
“…One study reported that lesions in breast cancer were observed to be reduced in all lesions after the two NAC cycles compared to pre-NAC, but patients with poor response (Residual malignant cell ≥ 70%)to treatment were found to have increased tumor volume after the third NAC cycle, but still smaller than pre-NAC [5]. Li et al reported that BC masses in the pCR group had smaller maximum diameter and had ultrasound features such as clear borders and lateral acoustic shadowing, which also found that smaller breast lesions before NAC were more likely to obtain pCR [6][7][8], and the rate of maximum diameter reduction of the mass and the proportion of echogenicity was significantly higher in the pCR group compared to the non-pCR group after NAC [6][9], which is statistically significance.…”
Section: Conventional Ultrasound For Response Evaluation To Nacmentioning
confidence: 99%
“…Li et al reported that BC masses in the pCR group had smaller maximum diameter and had ultrasound features such as clear borders and lateral acoustic shadowing, which also found that smaller breast lesions before NAC were more likely to obtain pCR [6][7][8], and the rate of maximum diameter reduction of the mass and the proportion of echogenicity was significantly higher in the pCR group compared to the non-pCR group after NAC [6][9], which is statistically significance. Dobruch-Sobczak et al reported that changes in lesion echogenicity (from hypoechoic to isoechoic or mixed echogenicity) were highly correlated in distinguishing pCR from non-pCR, and persistent hypoechogenicity of the lesion after the third NAC cycles predicted a non-pCR outcome in patients with postoperative pathology [5]. Pre-NAC lesions had a dense distribution of tumor cells with better conduction capacity than normal breast tissue, and Gray-scale ultrasound showed lower echogenicity of the lesions.…”
Section: Conventional Ultrasound For Response Evaluation To Nacmentioning
confidence: 99%